Characterization, histopathology and immunogenicity of the lumpy skin disease virus isolated during 2019–20 in Bangladesh - Uddin, Mohammad Asir; Hossain, Muhammad Tofazzal; Rahman, A. K. M. Anisur; Siddique, Mahbubul Pratik; Kafi, Md. Abdul; Hossain, Md. Golbar; Chakraborty, Sourav; Rahman, Mohummad Muklesur; Khasruzzaman, A. K. M.; Ward, Michael P.; Islam, Md. Alimul (Frontiers in Microbiology, 2024)
Lumpy skin disease (LSD) is a highly contagious vector-borne viral disease of cattle. LSD has emerged in Bangladesh in 2019, causing significant economic losses due to its high morbidity and mortality. This research was designed to isolate, identify, and assess the immunogenicity of LSD virus (LSDV) using nodular tissue samples obtained from affected cattle during the 2019-20 outbreak across nine districts of Bangladesh. To determine the presence of LSDV in nodular tissues, we initially used iiPCR and PCR, followed by histopathological examination. 151 were positive via iiPCR and PCR among the 180 collected samples. The PCR positive 151samples were then inoculated into 10-day-old embryonated chicken eggs via the CAM route to isolate LSDV, confirmed through PCR.Subsequently, partial sequencing and phylogenetic analysis of the P32 gene were performed to determine the origin of the circulating LSDV strain. The immunogenicity of selected LSDV strains was assessed through an ELISA test. The PCR results revealed a distinct positive band at 192 bp in both the nodular tissue samples and the LSDV isolated from chicken embryo inoculations. Microscopic analysis of the nodular lesions revealed thickening of the epidermis, ballooning degeneration of keratinocytes, and proliferation of follicular epithelia. Additionally, mononuclear infiltration was observed at the demarcation line between infected and healthy tissue, with necrosis of muscular tissues beneath the epidermis.The LSDV isolate from Bangladesh exhibited a close genetic relationship with LSDV strains isolated from neighboring and other regional countries including India, Myanmar, and Mongolia. This observation strongly suggests the possibility of a transboundary spread of the LSD outbreak in Bangladesh during 2019-2020. The results of the immunogenicity test showed that the serum antibody titer remained at a protective level for up to 18 months following secondary immunization with inactivated LSDV antigen. This finding suggests that the inactivated LSDV antigen could be a potential vaccine candidate to protect cattle in Bangladesh against LSDV. Our research successfully isolated, identified, and characterized LSDV in cattle nodular tissues from the outbreak sin Bangladesh. Furthermore, it provided insights into the probable origin of the circulating strain and investigated a potential vaccine candidate to protect cattle in the region from LSD.